مضاربت اور شریعت اسلامیہ عصری مسائل کی روشنی میں تجزیاتی مطالعہ: Modaraba and Islamic Sharia Analytical Studies in the light of Contemporary Problems (Khairulummah, 2023)
Madarabat is an agreement of mutual aid & cooperation. There are two types of Madarabat (1) Madarabat Muqadida and (2) Madarabat Mutaliqa. This method of trade due to its characteristics was practiced even before Islam and continued even after Islam. The Prophet Muhammad (P.B.U.H) worked with Bibi Khadija on madarabat. Hazrat Muhammad (p.b.u.h) took Bibi Khadija's goods for sale to different markets and areas. The companions of Muhammad (p.b.u.h) while preaching Islam also used the same way of trade and invested in other remote areas. Seeing its usefulness, other religions also adopted this method of trade for a long. Since this method negates usury, those who wanted to avoid interest, adopted this method of business/trade. In this way of business/trade, one is called Rab-ul-Maal (investor), and the other is called Mudarab. Madarab is a person who knows how to do business, but he does not have the capital to invest, and the Rab-ul-Maal (investor) has capital, but he does not have the skills to do business. In Madarabat each party has certain conditions and shari'ah rights and duties. We can see the Mudarabat in the contemporary era in different new forms. These include business financing, microfinancing, self-employment scheme, mutual fund, company share, Islamic banking, Islamic Sukuk and Takaful, etc
Keywords: Teaching of Islam, Madarabat, Investor, Business, Cooperation, Trade, Goods